Lecturers' Attitudes towards English Varieties Exposure in Indonesia (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This study was established from the lack of research of English varieties concept in Indonesia. In this study, the lecturers' attitude toward the English varieties is explored as well as their view about using the English varieties in the classroom. The study used a qualitative research design to seek the participants' attitude toward the varieties. The subjects of the study are ten lecturers of three universities in Surabaya; they are two private and one state university with ten lecturers in total. The researcher used prompt-production to explore in-depth lecturers' attitude. One of the most significant findings to emerge from this study is the differences between the international graduated lecturers and national graduated lecturers in terms of their attitude toward the English varieties. Furthermore, this attitude also influences their perception about teaching the varieties in English language teaching (ELT) classroom.